Performance Investigation of the Micro-Hole High-Speed Aerostatic Thrust Bearing Based on the Finite Element Method - Siyu Gao; Tianle Jiang; Zhuang Li; Hongbin Yang; Min Zhu; Youyun Shang; Laiyun Song; Lihua Lu; Qiang Gao; Hanqian Zhang (Machines)
Micro-hole aerostatic bearings have emerged as critical components in ultra-precision machining systems, offering a superior load capacity, stiffness, and stability compared to traditional orifice-based designs. These enhancements are primarily attributed to the high-density configurations of micro-holes and the reduction in hole diameter. However, research on the design and analysis of micro-hole aerostatic bearings for high-rotational-speed applications remains limited. In this study, the finite element method (FEM) was employed to solve the Reynolds equation, thereby conducting a systematic evaluation of the static and high-speed performance characteristics of micro-hole aerostatic thrust bearings. The effects of restrictor types, micro-hole layouts, structural parameters, and centrifugal deformation under high-rotational-speed conditions on bearing performance have been comprehensively examined. The objective of this study is to provide a basis for the design of micro-hole high-speed aerostatic spindles.